Vulvar malignant melanoma: a case report and review of management - Maizatulernawani Hashim; Nor Hidayah Yayanto; Badrul Zaman Muda Abdullah; Fathi Ramly; Rahimah Abd Rashid; Daniel Roza Duski (PAGEPress Publications, 2022)
Background: Vulvar malignant melanoma (VMM) is uncommon and pose a significant management challenge. Here, we presented a case of VMM managed by surgery, chemoradiation and planned for targeted therapy.  Case Report: A 70 years old woman with underlying diabetes mellitus and hypertension presented with black-coloured growth around her left vulva for two months. Initial biopsy confirmed malignant melanoma with positive staining for S100, HMB 45, and Melan A. Imaging study showed localized disease to the vulva. Result: She underwent bilateral radical vulvectomy and bilateral inguinofemoral lymph nodes dissection followed by radiotherapy. She had locoregional disease recurrence, which was subsequently managed by palliative perineal radiotherapy, chemotherapy and planned for immunotherapy. Conclusion:  Vulvar malignant melanoma is a rare and aggressive tumour, with a poor overall prognosis and high recurrence rate. Adjuvant chemotherapy, radiotherapy and immunotherapy may benefit for local recurrence and distant metastasis cases. Molecular Analysis has a potential role in targeted therapy to improve the survival and outcome of the patient.